Food safety governance in Saudi Arabia: Challenges in control of imported food. Issue 1 (13th December 2020) - Alrobaish, Waeel Salih; Vlerick, Peter; Luning, Pieternel A.; Jacxsens, Liesbeth
Abstract: The operating environment for food safety interventions in nations such as Saudi Arabia, with limited local agricultural productivity, high reliance on foreign food imports and observance of Islamic laws, is remarkably challenging for the national control and regulatory institutions, since compliance to the mandatory food safety regulations and the local religious Halal standards must be ensured. This review offers a comprehensive analysis of the recently restructured food safety governance in Saudi Arabia from the perspective of its food imports control. Specifically, the nature of the food imports, the organization of the food safety governance and the current control practices of imported food, in consideration of food safety and Halal requirements, are analyzed through a triangulation of data and information from secondary sources (academic literature review and gray literature search) and primary sources (direct consultation of field experts). Statistical trade data on imported food were also performed. Results revealed that the process of centralizing all the control and regulatory activities under a single agency, which the government started to strengthen the national food safety governance, has not been completed yet. The resulting overlap of legislative and monitoring tasks by multiple entities augments the challenge of ensuring the safety, quality, and authenticity of imported food and their compliance to Halal standards. The vulnerabilities and challenges still to be addressed by the local food industry and the public sector are discussed, with implications for national and international field practitioners and policymakers of countries facing similar challenges.